Education in Indonesia's Regional Economic Development Before Fiscal Decentralization - Kawuryan, Anna Maria Siti (Jurnal Ekonomi dan Pembangunan Indonesia, 2002)
Indonesia is a diverse country with uneven resource endowment across its provinces. This study examines the effects of human capital investment policies on the promotion of more equitable income growth across provinces. First, the rate of return to education is estimated for each province using the 1976 and 1989 Indonesian National Labor Force Surveys (SAKERNAS). Then, regional economic indicators are used to explain differences in the rates of return to education among provinces and to develop and test hypotheses regarding the contribution of investment in education to personal income growth in different regions in Indonesia. The study finds large differences in the rates of return to education among provinces with the highest rates of return in the poorest provinces. A model of segmented regional labor markets is advanced to explain why wage differences across provinces may exist. The estimates suggest that labor market segmentation was more pronounced for un- or low-educated workers because inter-provincial differences in wages were greater among this group than among more educated workers. Education may reduce regional labor market segmentation. More educated workers may be better able to compete for jobs in other provinces, and therefore more mobile, because they possess the needed language and market skills. Thus, it appears that education not only enhances personal (and national) income, but also promotes greater equity across provinces. Equitable investment in education across provinces is compatible with both equity and efficiency goals in regional economic development.